KONFLIK KEYAKINAN HAKIM: ANALISIS PERBANDINGAN CONVICTION INTIME DI PRANCIS DAN CONVICTION RAISONNÉE DI PORTUGAL - Zul Khaidir Kadir (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The criminal evidence systems in France and Portugal reflect two contrasting approaches in the civil law tradition, namely conviction intime and conviction raisonné. However, the fundamental debate between the two triggers dynamics regarding how the evidentiary system balances judicial independence and transparency. This study aims to analyze the philosophical differences and implications between the two principles. This study uses a normative legal research method with a comparative approach. The data collection method is collected using library research, then analyzed qualitatively and presented descriptively. The results of the study indicate that there is no single approach that can fully meet the needs of flexibility, efficiency, and transparency in criminal evidence. Both conviction intime in France and conviction raisonnée in Portugal present unique advantages and disadvantages, but both can complement each other if applied in a balanced manner.